2020
DOI: 10.2147/ott.s264616
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of Genomic Alterations of Perineural Invasion in Patients with Stage II Colorectal Cancer</p>

Abstract: Purpose The molecular mechanism of perineural invasion (PNI) in stage II colorectal cancer (CRC) remains not to be defined clearly. This study aims to identify the genomic aberrations related to PNI in stage II CRC. Patients and Methods Using array-based comparative genomic hybridization (array-CGH), primary tumor tissues and paracancerous normal tissues of stage II CRC with PNI and without PNI were analyzed. We identified genomic aberrations by using Genomic Workbench … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies have found that SLC20A2 is associated with perineural invasion in stage II colorectal cancer. [ 35 ] SLC35E1 belongs to the solute carrier family 35. This gene has been reported to be associated with the recurrence of papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that SLC20A2 is associated with perineural invasion in stage II colorectal cancer. [ 35 ] SLC35E1 belongs to the solute carrier family 35. This gene has been reported to be associated with the recurrence of papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…27 Compared with PNI-positive patients, the expression of FLT1, FBXW7, FGFR1, SLC20A2, and SERPINI1 was significantly up-regulated in PNI-negative group. 28 However, detailed molecular mechanism of TD and PNI still remains unclear.…”
Section: Discussionmentioning
confidence: 99%